The Rationality of Emergency Consumption by Muslim Consumers in the Perspective of Sharia Microeconomics - Mulyani, Hilda; Wiqiyan, Khalid; Tiawarman, Olivia Angelica; Adiman, Adiman; Elvira, Rini (RIGGS: Journal of Artificial Intelligence and Digital Business, 2026)
Emergencies such as disease outbreaks and global food crises challenge the basic assumptions of Islamic microeconomics regarding Muslim consumer preferences, which are bound by the certainty of halal. In the face of limited supplies and threats to life, Muslim consumers are faced with a dilemma between compliance with halal principles and the fulfillment of emergency needs. This article analyzes changes in Muslim consumer rationality in emergency conditions by placing it within the framework of Islamic microeconomics. The study uses a literature review method with a conceptual-analytical approach to Islamic consumption theory, the concepts of maslahah and maqashid al-shariah, as well as the dynamics of supply and demand in crisis situations. Under normal circumstances, haram goods do not form a demand curve due to sharia prohibitions. However, when an emergency threatens life and there are no halal alternatives available, a demand point emerges, which is an incidental demand point that is not influenced by price and only reflects the minimum requirements to maintain safety of life. Rationality is not oriented towards maximizing utility, but rather towards protecting maqashid, especially hifz al-nafs. Emergency consumption is temporary, limited, and does not change the original law of prohibition. This study offers a demand point framework as an improvement to demand analysis in Islamic microeconomics while also providing policy implications for strengthening the halal product assurance system so that it can respond to crises without compromising Sharia integrity.